PENGARUH PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA PENYULUH PERTANIAN PADA BKP5K KABUPATEN BOGOR - Sinaga, Herty Ramayanti (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2018)
One way to improve the quality of agricultural extension resource through education and training is implemented out in a planned and systematic. In other words, the importance of education and training within the organization is to improve the performance of agricultural extension that include the knowledge and skill that support, as well as the building of the attitude of each of the extension as desired by organization. This study aims to analyze the influence of training and education on the performance of agricultural extension workers in the Food Security and Managing Extension Agriculture, Fisheries and Forestry (BKP5K) Bogor and analyze the indicators that reflect the dominant success of the training and education provided to the agricultural extension. Sampling is based on non-probability sampling technique using purposive sampling method of 79 samples from 99 populations of agricultural extension agricultural extension PNS. These results indicate that 1) the influence of training and education on the performance of agricultural extension, the training negatively affect the performance of agricultural extension and education have positive influence on the performance of agricultural extension; and 2) the dominant indicator of the training variables contained in the first indicator, namely the training  suitability of the materials needed with this type of training with the results of 3.28. Dominant indicator of educational variables contained in the second indicator, namely the educational suitability of the current work with the results of 3.28. Dominant indicator of performancel variables contained in the first indicator, namely understand the program with the results of 3.23.